Studi Kesejahteraan Kucing Peliharaan di Beberapa Toko Hewan Peliharaan (Pet Shop) - Nanda Puspitasari; Rizwar Rizwar; Jarulis Jarulis; Darmi Darmi; Apriza Hongko Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the welfare conditions of cats kept in several pet shops in Bengkulu City, especially regarding eating and drinking, health, comfort and contact with other cats. The method used is direct observation (direct survey) and interviews with pet shop owners or servers. The data obtained were analyzed by calculating the percentage of pet shops that pay attention to the welfare of cats and those that do not. The results showed that the cat is eating welfare obtained an average percentage of 83.3%, drinking 66.7%, health 88.9%, comfort 100% and contact with other cats 58.3%. In conclusion, the pet shop in Bengkulu City meets cat welfare standards in aspects of eating, drinking, health, comfort, and contact with other cats. Keywords: Animal Welfare, Cats, Bengkulu City, Pet shop